2021
DOI: 10.3390/cells10061384
|View full text |Cite
|
Sign up to set email alerts
|

PKA and PKC Balance in Synapse Elimination during Neuromuscular Junction Development

Abstract: During the development of the nervous system, synaptogenesis occurs in excess though only the appropriate connections consolidate. At the neuromuscular junction, competition between several motor nerve terminals results in the maturation of a single axon and the elimination of the others. The activity-dependent release of transmitter, cotransmitters, and neurotrophic factors allows the direct mutual influence between motor axon terminals through receptors such as presynaptic muscarinic ACh autoreceptors and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In previous studies, we found that during the first postnatal days (P5–P9), PKA and PKC have opposed effects in delaying and favoring, respectively, synapse maturation [ 3 , 35 , 45 , 49 ]. Here, we evaluate the strength of the hypothesis of the close relation between the effect of these serine/threonine kinases and VGCCs for developmental axonal competition and loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we found that during the first postnatal days (P5–P9), PKA and PKC have opposed effects in delaying and favoring, respectively, synapse maturation [ 3 , 35 , 45 , 49 ]. Here, we evaluate the strength of the hypothesis of the close relation between the effect of these serine/threonine kinases and VGCCs for developmental axonal competition and loss.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we evaluate the strength of the hypothesis of the close relation between the effect of these serine/threonine kinases and VGCCs for developmental axonal competition and loss. We repeated some experiments of PKA and PKC stimulation or inhibition of the previously cited paper Garcia et al [ 49 ] and compared them with those obtained after VGCC stimulation or inhibition. PKA and PKC modulation of VDCCs has been determined, and phosphorylation sites of functional relevance are known for the three L-, P/Q-, and N-type VDCCs [ 50 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found [ 88 ] that PKC favors axon loss through cPKCβI and nPKCε isoform activity (as judging by the effect of their general [Bry-1 or PMA] and specific activators [dPPA, FR236924] and inhibitors [βIV 5–3 and εV 1–2 ] respectively) whereas PKA-I and II activity (as judging by the effect of their specific blockers [H-89, Rp8-Br, and Rp-cAMPs] and activator [Sp8Br], respectively) delay axonal loss in P9 mice. Furthermore, no significant differences exist between the effects of PKA activators and PKC inhibitors, or between PKA inhibitors and PKC activators, on changing axon loss rate [ 25 ]. Moreover, a similar level of PKA inhibition and PKC potentiation (mainly of the cPKCβI and nPKCε isoforms that are strictly localized on the presynaptic site [ 89 – 91 ]) seems to be required to advance in axonal loss, clearly suggesting the complementarity of these kinases.…”
Section: Machr Coupling To Serine Kinases During Synapse Eliminationmentioning
confidence: 99%
“…During development, skeletal myocytes start polyinnervated by several axons [15][16][17], but after their competitive interactions, neuromuscular junctions (NMJ) finally become innervated by only one axon [6,13,14,18]. There are many reviews about synapse elimination mainly focused on the NMJ [1,[18][19][20][21][22][23][24][25][26][27]. Several relevant cues of the molecular and cellular mechanisms involved in the elimination of supernumerary nerve terminals have been investigated and collected in the cited reviews.…”
Section: Introductionmentioning
confidence: 99%